2021
DOI: 10.3390/ijerph18084134
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Damage and Performance after Single and Multiple Simulated Matches in University Elite Female Soccer Players

Abstract: The present study aimed to compare changes in muscle damage and performance parameters after playing single versus multiple soccer matches to examine fixture congestion effects on performance. Twelve elite female university soccer players performed single, three and six consecutive 90-min bouts of the Loughborough Intermittent Shuttle Test (LIST) with ≥12-weeks between conditions in a pseudo-randomized order. Heart rate, blood lactate, rating of perceived exertion and covering distance in each LIST were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…As discussed above, most Zn is found in skeletal muscle (~60%), whereas only ~0.1% of body Zn is found in plasma [ 62 ]. Secondly, this is due to the muscle damage produced during soccer practice generated by the predominant physical actions (accelerations, decelerations, changes of direction) and trauma due to collisions and impact [ 63 , 64 ]. It is known that there are differences between genders in the physical demands during a match, with more actions of greater intensity in men’s matches [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, most Zn is found in skeletal muscle (~60%), whereas only ~0.1% of body Zn is found in plasma [ 62 ]. Secondly, this is due to the muscle damage produced during soccer practice generated by the predominant physical actions (accelerations, decelerations, changes of direction) and trauma due to collisions and impact [ 63 , 64 ]. It is known that there are differences between genders in the physical demands during a match, with more actions of greater intensity in men’s matches [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding football, a vast number of studies conducted in male and female semi-professional and professional football players have reported values of CK as a means to assess EIMD in training and competition ( Andersson et al, 2008 ; Gravina et al, 2011 ; Rampinini et al, 2011 ; Thorpe and Sunderland, 2012 ; Gatterer et al, 2013 ; Gunnarsson et al, 2013 ; Nedelec et al, 2013 ; Silva et al, 2013 ; Souglis et al, 2015a ; Pimenta et al, 2015 ; Russell et al, 2015 ; Mohr et al, 2016 ; Bouzid et al, 2018 ; Henrique et al, 2018 ; Marques-Jimenez et al, 2018 ; Souglis et al, 2018 ; Sparkes et al, 2018 ; Botelho et al, 2020 ; Pooley et al, 2020 ; Chou et al, 2021 ; Csala et al, 2021 ; Daab et al, 2021 ; Garcia-Romero-Perez et al, 2021 ; Hacker et al, 2021 ; Khaitin et al, 2021 ; Kostrzewa-Nowak et al, 2021 ; Trecroci et al, 2021 ; Selmi et al, 2022 ). Of note, as susceptibility to EIMD is higher among players unaccustomed to eccentric exercise, returning to high-intensity training and competition from off-season and periods of recovery from injury are considered critical time points for monitoring ( Nédélec et al, 2012 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
“…On this subject, Garcia-Romero-Perez et al (2021) showed that pre-match CK levels are significantly higher among players exposed to > 60 min of match-play during congested compared to non-congested periods, thus representing an important aspect to consider when deciding on availability of players across matches ( Garcia-Romero-Perez et al, 2021 ). Chou et al (2021) reported in female players that three and six Loughborough Intermittent Shuttle Tests (LIST) played in consecutive days induced a higher increase in CK blood levels compared to a single LIST, which was suggestive of accumulation of muscle damage across tests ( Chou et al, 2021 ). However, the recovery rate remained unchanged, which was proposed to denote attenuated magnitude of EIMD over multiple LISTs as a consequence of the repeated bout effect ( Chou et al, 2021 ).…”
Section: Biomarkers Of Post-match Recovery In Footballmentioning
confidence: 99%
“…The strengths of the current prospective cohort study include that it was conducted in a professional soccer club in the English Premier League for two consecutive seasons. In contrast to previous cross-sectional studies [6] or short-term prospective studies, we have assessed a total of 22 multi-match and 33 single-match weeks. Secondly, considering the fact that CK responses in soccer players are individualized (Silva et al 2014), it is noteworthy to point out that it involved the same players for both seasons, although it reduced the sample size because new players were not included in data from the second season.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is widely accepted that kinetic models predict higher overall injury burden for successful teams competing in both national and European club competitions [4]. It is important to take into account that even a recovery period of 72 h post-match may not be long enough to completely restore the homeostatic balance in soccer players [5,6].…”
Section: Introductionmentioning
confidence: 99%